Atividade antitumoral da berberina em células de neuroblastoma SH-SY5Y - Lenz, Luana Suéling (2017)
Neuroblastoma is the most common tumor found in the first year of life and represent 6% of the all childhood cancers. There is few options of treatment and the mortality is close to 21%, or exceeds 50% between the high risk cases the mortality. Berberine (BBR) is an alkaloid used in traditional Chinese medicine for a long time and several studies have proved a diversity of pharmacological activities from this compound, among them antitumoral. Therefore, this molecule may have potential to the treatment of neuroblastoma. The aim of this study was to evaluate whether BBR has antitumoral activity in SH-SY5Y neuroblastoma cell lineage, as well as, investigate if the mechanism trigger is through ERO induction, AMPK and p53 activation. First of all, it was performed a cell death assay with several different concentration of BBR. From this data, we identify the minor concentration able to lead cell to death, which was used in the next experiments. In cells treated or not with BBR and/or an AMPK inhibitor (Compound C), it was determined the apoptotic index and cell cycle measure, as well as labeling with specific antibody to quantify the phosphor-p53 and caspase 3. In the same way, the migration and forming colony ability, ERO levels, activity of antioxidant enzymes and oxidative damage on DNA was detected. Still, it was done q-PCR to quantify the expression of p53, bax, bcl-2, caspase-3 and antioxidant enzymes genes. Our results prove that BBR do not alter cell cycle in cell line studied, unlike the results from other researches, but increase the apoptotic cells and the levels of p-p53 independent of AMPK activity, besides causing an increase in ERO levels and catalase activity. Also, it was detected a decrease in migratory and forming colony ability in the cells treated. This study suggest that BBR have therapeutic potential as an adjuvant in neuroblastoma treatment.